ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KETERSEDIAAN BERAS DI INDONESIA - Ahmad Ilyas; Melinda Noer; Ira Wahyuni (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Rice is a strategic food commodity in Indonesia. Disruption to the availability of rice will disrupt economic, social and political stability in Indonesia. This research aims to see a general picture of rice availability in Indonesia, as well as identify and analyze factors that influence availability. This study uses secondary data in the form of time series data for 14 years from January 2004 to December 2017. The data is processed using descriptive analysis and path analysis using the Statistical Data Analysis (STATA) program. General description of the development of rice availability in Indonesia shows an increase every year with a growth of 3.39%. The increased availability was supported by 'policies issued by the government such as policies in the production sector in the form of input subsidies (seeds and fertilizers), facilities and infrastructure, subsidized outputs for Government Purchasing Prices (HPP), the import sector in the form of import regulations and import tariffs. Based on a path analysis of the model of Indonesian rice availability, production and imports have a direct and significant effect on the availability of rice in Indonesia